Semantics-guided procedural rendering for woodcut maps - Adabala, Neeharika; Toyama, Kentaro (CVPR 2005, 2005)
We present a technique for taking a vector representation of geographical features as input and rendering a map in the style of antique woodcut maps. The patterns are created with procedural approaches that depend on the semantic labeling of each vector element, with, for example, mountain ranges drawn differently from coastlines. The technique can be used to create stylistic visualizations of maps, for games and other applications that seek to set a mood when displaying geographical information.